Preparation method and application of graphite carbon catalyst
By preparing graphite carbon catalysts, and using them to activate persulfate to selectively release singlet oxygen, the problem of catalytic activity inhibition under high salinity conditions is solved, and efficient oxidation and degradation of difficult-to-degradation pollutants such as organic dyes and antibiotics is achieved, and good environmental adaptability and cycling performance are achieved.
Patent Information
- Application Number
- CN202310151564.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-22
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-02-22
AI Technical Summary
Under high salinity conditions, the catalytic activity of advanced oxidation techniques based on sulfate radicals in oxidative degradation of organic pollutants is inhibited, and the prior art is difficult to effectively degrade difficult-to-degraded pollutants such as organic dyes and antibiotics.
By preparing a graphite carbon catalyst, organically synthesized using materials such as p-nitrobenzaldehyde and pyrrole, a catalyst that can release singlet oxygen 100% selectively is obtained, which is used to activate persulfate and efficiently oxidize and degrade organic pollutants.
It has achieved efficient oxidation and degradation of difficult-to-degradation pollutants such as AO7, Orange II and antibiotics under high salinity conditions. It also has excellent environmental adaptability and cycling performance, and can adaptively degrade most pollutants and reuse them.
Smart Images

Figure CN116216709B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and specifically relates to a preparation method of a graphite carbon catalyst and application thereof. Background Art
[0002] In the past two decades, advanced oxidation treatment technology, especially the advanced oxidation treatment technology based on permonosulfate (PMS) activation, has been considered as one of the most effective technologies for degrading organic pollutants. Sulfate radicals and hydroxyl radicals with high oxidation potential generated by the cleavage of the OO bond in PMS are the main active oxygen species for effective oxidation and degradation of organic pollutants.
[0003] However, under high salinity conditions, the catalytic activity of sulfate radical-based advanced oxidation technology in the oxidative degradation of organic pollutants is severely inhibited. Singlet oxygen has attracted much attention due to its long life cycle, electrophilicity and excellent oxidative properties. It has been widely used in photooxidative catalysis, photodynamic therapy and oxidative degradation of organic substrates.
[0004] Singlet oxygen is mainly synthesized from ordinary oxygen through photosensitized reaction. In recent years, graphene or graphene-like carbon nanomaterials (such as nanosheets, nanospheres, nanorods, nanotubes, nanodots, etc.) as metal-free and environmentally friendly materials are considered to be efficient and green catalysts for the selective generation of singlet oxygen by persulfate activation. Summary of the invention
[0005] The present invention provides a preparation method of a graphite carbon catalyst and application thereof. The catalyst can be used to activate peroxymonosulfate and selectively release a large amount of singlet oxygen with 100% selectivity, thereby efficiently oxidizing and degrading organic dyes such as AO7 and Orange II and difficult-to-degrade pollutants such as antibiotics.
[0006] The technical solution of the present invention is a method for preparing a graphite carbon catalyst, comprising the following steps:
[0007] Step 1, mixing p-nitrobenzaldehyde and pyrrole to prepare a mixed solution;
[0008] Step 2, heating propionic acid to boiling, adding the mixed solution obtained in step 1 under reflux stirring, heating and boiling for 1-2 hours, and cooling naturally after the reaction is completed;
[0009] Step 3, adding methanol to the solution of step 2, mixing, letting stand, filtering, washing and collecting the filter cake;
[0010] Step 4: The solid obtained in step 3 is vacuum dried, and then graphitized at 600-900°C, and the obtained material is washed with water and then dried to obtain the graphite carbon catalyst TNPP. The preferred calcination temperature is 800-850°C.
[0011] Furthermore, in step 1, the molar ratio of p-nitrobenzaldehyde to pyrrole is 1:(1-2).
[0012] Furthermore, in step 2, the volume ratio of propionic acid to the mixed solution is: (10-12.5):1.
[0013] Furthermore, the standing time in step 3 is 6-8 hours.
[0014] Furthermore, in step 3, washing is performed repeatedly with methanol and acetone solutions respectively.
[0015] Furthermore, in step 4, the vacuum drying temperature is 50-60° C., and the drying time is 6-8 h.
[0016] Furthermore, during calcination in step 4, the material is placed in a furnace, and then the temperature is increased at 2-5°C / min, and after the temperature reaches the target temperature, the temperature is maintained constant for 2-4 hours.
[0017] The present invention also relates to a graphite carbon catalyst prepared according to the above method.
[0018] The invention also relates to the application of the catalyst in activating peroxymonosulfate to degrade organic pollutants.
[0019] Furthermore, the organic pollutants include organic dyes AO7, Orange II, Reactive Blue 19, Methyl Orange, Reactive Red 2 and antibiotics.
[0020] The present invention has the following beneficial effects:
[0021] The present invention prepares tetranitrophenyl porphyrin by organic synthesis, and then obtains a novel carbon catalyst through calcination, washing and drying. The novel carbon catalyst can be used to activate peroxymonosulfate and selectively release a large amount of singlet oxygen with 100%, thereby efficiently oxidizing and degrading organic dyes such as AO7 and Orange II and difficult-to-degrade pollutants such as antibiotics. The novel carbon catalyst has excellent environmental adaptability and circulation performance, can adaptively degrade most pollutants and can be reused, and has excellent environmental adaptability and circulation performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The scanning electron diffraction patterns of catalysts a, b, c, and d prepared in Comparative Examples 1, 2, 3 and Example 1 are shown.
[0023] Figure 2 This is a comparison of the UV-visible absorption spectra of catalysts a, b, c, and d catalyzing PMS to produce active oxygen species to degrade AO7.
[0024] Figure 3This is a comparison of the UV-visible absorption spectra of TNPP catalyzing PMS to produce active oxygen species to degrade AO7 at different calcination temperatures prepared in Example 3.
[0025] Figure 4 This is a comparison chart of the adsorption effects of TNPP800 and TNPP900 prepared in Example 3 on AO7.
[0026] Figure 5 This is the scanning electron diffraction pattern of TNPP700, TNPP800 and TNPP900 prepared in Example 3.
[0027] Figure 6 It is a comparison chart of the ultraviolet-visible absorption spectra of the graphite carbon catalyst TNPP prepared in Example 1 for activating PMS to produce singlet oxygen to degrade AO7, RR2, MO, and RB19.
[0028] Figure 7 This is a graph of the catalytic degradation rate of the graphite carbon catalyst TNPP prepared in Example 1 after three repeated cycles. DETAILED DESCRIPTION
[0029] The embodiments of the present invention will be described in detail below with reference to examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention.
[0030] Comparative Example 1:
[0031] 300 mg of tetrahydroxyphenylporphyrin (THPP) was placed in a muffle furnace and calcined at 800°C for 4 h. The solid sample obtained after calcination was washed with water several times and dried to obtain catalyst a.
[0032] Comparative Example 2:
[0033] 300 mg of tetraphenylporphyrin (TPP) was placed in a muffle furnace and calcined at 800 °C for 4 h. The solid sample obtained after calcination was washed with water several times and dried to obtain catalyst b.
[0034] Comparative Example 3:
[0035] 300 mg of tetracarboxyphenylporphyrin (TCPP) was placed in a muffle furnace and calcined at 800° C. for 4 h. The solid sample obtained after calcination was washed with water several times and dried to obtain catalyst c.
[0036] Embodiment 1:
[0037] Step 1, mix 6.0 g of p-nitrobenzaldehyde and 3.76 mL of pyrrole in a beaker;
[0038] Step 2, take 40% propionic acid mLAdd to a round-bottom flask and heat to boiling. Add the mixed solution obtained in step 1 under reflux stirring, heat to boiling and react for 2 h. After the reaction is completed, cool naturally to 60°C.
[0039] Step 3, adding methanol to the solution of step 2 and letting it stand for 8 hours, then filtering with suction, washing the product and separating the solid;
[0040] Step 4, vacuum drying the solid obtained in step 3 at 60°C, placing the obtained product in a muffle furnace and heating it to 800°C at 5°C / min and calcining it for 4 h, washing the obtained product with water and drying it to obtain a graphite carbon catalyst, namely catalyst d.
[0041] The catalysts a, b, c, and d obtained in Comparative Examples 1 to 3 and Example 1 were scanned by electron microscope. Figure 1 It can be observed that the surfaces of catalysts b and d are porous structures, while the surfaces of catalysts a and c are non-porous. The porous structure can provide more active sites, so catalysts b and d can more efficiently activate PMS to degrade pollutant AO7. The surface of catalyst d is nitrogen-rich. The increase in surface nitrogen content can increase the crystallinity of the active crystal surface, increase the bandgap width during the synthesis process, increase the absorption of visible light, and accelerate the degradation rate.
[0042] Embodiment 2:
[0043] The catalysts a, b, c, and d of comparative examples 1, 2, and 3 and embodiment 1 of the present invention are used to catalyze the degradation of PMS by AO7 (AO7).
[0044] The steps of the above catalyst catalyzing the degradation reaction of PMS to AO7 are as follows:
[0045] Step 1: Take 4 round-bottom flasks, add AO7 solution (50mL, 50mg / L), and then add catalyst a, b, c or d to different flasks respectively. The amount of catalyst added to each flask is 12.5mg, and stir for 10min after adding;
[0046] Step 2: Test and record the absorption peak of AO7 at this time;
[0047] Step 3: Quickly add PMS (0.5 g / L) into the round-bottom flask, take out 3 mL at 0 min, 1 min, 3 min, 5 min, 10 min, 15 min, and 20 min respectively, and add it into the cuvette, and measure the peak shape of the UV-visible absorption spectrum of AO7 with a UV-visible photometer.
[0048] The UV-visible absorption spectra of the degradation of AO7 by PMS produced by catalysts a, b, c, and d are shown in the figure. Figure 2The catalytic effect was determined by detecting the characteristic peak of AO7 at a wavelength of 480 nm using a UV-visible spectrophotometer. Sampling was performed at different time intervals, and the reaction was terminated when the peak value of the characteristic peak of AO7 at a wavelength of 480 nm no longer decreased.
[0049] Catalysts a and c do not have good degradation effects and cannot be used for pollutant degradation. The degradation rate of catalyst b for AO7 is lower than that of catalyst d. Due to the competition and synergy of non-covalent bond interactions, π-π stacking, the degree of intermolecular interaction will be different, resulting in different nanomorphologies. The different electron-donating and electron-withdrawing abilities of the meso-position substituents of porphyrin molecules play a very important role in regulating and controlling the self-assembly process of porphyrin molecules. Among them, TNPP is a porphyrin in which all four meso-positions are substituted by nitro groups, and its electron-withdrawing ability is the strongest, making the structure of catalyst d more porous to provide more active sites, so catalyst d exhibits the best catalytic effect.
[0050] Embodiment 3:
[0051] Steps 1 to 3 are the same as in Example 1, except that the products obtained after vacuum drying in step 4 are placed in a muffle furnace and calcined at 600° C., 700° C., 800° C., and 900° C. for 4 h, respectively, and the obtained products are washed with water and dried to obtain catalysts, which are respectively recorded as TNPP600, TNPP700, TNPP800, and TNPP900.
[0052] The UV-visible absorption spectra of TNPP prepared at different calcination temperatures in Example 3 catalyzing PMS to produce active oxygen species to degrade AO7 are shown in the following figure. Figure 3 The catalytic effect was measured by UV-visible spectrophotometer to detect the characteristic peak of AO7 at a wavelength of 480 nm. Sampling was performed at 0 min, 1 min, 3 min, 5 min, 7 min, 9 min, 11 min, 13 min, 15 min, and 20 min, respectively. The reaction was terminated when the peak value of the characteristic peak of AO7 at a wavelength of 480 nm no longer decreased.
[0053] TNPP600 and TNPP700 did not show good degradation effect.
[0054] Figure 4 This is a comparison chart of the adsorption effects of TNPP800 and TNPP900 prepared by the present invention on AO7. It can be seen from the figure that the main function of TNPP900 is adsorption, which is not conducive to converting AO7 into non-toxic small molecules, and the sewage treatment process is not green and environmentally friendly. Therefore, TNPP800 was selected as the optimal catalyst for further experiments.
[0055] Figure 5The SEM images of TNPP700, TNPP800 and TNPP900 show that the morphology changes with the increase of carbonization temperature. TNPP800 and TNPP900 present a honeycomb morphology, but TNPP900 has a larger pore size, which adsorbs more substrates and occupies more active sites, resulting in a significant reduction in its catalytic activity. Example 4:
[0056] The graphite carbon catalyst prepared by the present invention is used to generate singlet oxygen for the degradation of AO7.
[0057] The reaction mechanism of graphite carbon catalyst catalyzing PMS to produce active oxygen species to degrade AO7 is that in the presence of PMS, electrons are transferred through OO bond cleavage to activate PMS, thereby producing 1 O 2 Degradation of AO7.
[0058] The steps of the graphite carbon catalyst catalyzing PMS to produce singlet oxygen to degrade AO7 are as follows:
[0059] Step 1: Add AO7 solution (50 mL, 50 mg / L) into a 100 mL round-bottom flask, add catalyst (0.25 g / L) and stir for 10 min;
[0060] Step 2: Test and record the absorption peak of AO7 at this time;
[0061] Step 3: Quickly add PMS (0.5 g / L) into the round-bottom flask, take out 3 mL into the cuvette at 0 min, 1 min, 3 min, 5 min, 7 min, 9 min, 11 min, 13 min, and 15 min, and measure the peak shape of the UV-visible absorption spectrum of AO7 with a UV-visible photometer.
[0062] The mass of the catalyst in step 1 is 12.5 mg.
[0063] Example 5
[0064] The graphite carbon catalyst prepared by the present invention is used to generate singlet oxygen for the degradation of RR2.
[0065] The reaction mechanism of graphite carbon catalyst catalyzing PMS to produce active oxygen species to degrade RR2 is that in the presence of PMS, electrons are transferred through OO bond cleavage to activate PMS, thereby producing 1 O 2 Degrade RR2.
[0066] The steps of the graphite carbon catalyst catalyzing PMS to produce singlet oxygen to degrade RR2 reaction are as follows:
[0067] Step 1: Add RR2 solution (50 mL, 50 mg / L) into a 100 mL round-bottom flask, add catalyst (0.25 g / L) and stir for 10 min;
[0068] Step 2: Test and record the absorption peak value of RR2 at this time;
[0069] Step 3: Quickly add PMS (0.5 g / L) into the round-bottom flask, take out 3 mL at 0 min, 3 min, 5 min, and 10 min respectively and add it into the cuvette, and measure the peak shape of the UV-visible absorption spectrum of RR2 with a UV-visible photometer.
[0070] The mass of the catalyst in step 1 is 12.5 mg.
[0071] Example 6
[0072] The graphite carbon catalyst prepared by the present invention is used to generate singlet oxygen for the degradation of MO.
[0073] The reaction mechanism of graphite carbon catalyst catalyzing PMS to produce active oxygen species to degrade MO is that in the presence of PMS, electrons are transferred through OO bond cleavage to activate PMS, thereby generating 1 O 2 Degradation of MO.
[0074] The steps of the graphite carbon catalyst catalyzing PMS to produce singlet oxygen to degrade MO are as follows:
[0075] Step 1: Add MO solution (50 mL, 50 mg / L) into a 100 mL round-bottom flask, add catalyst (0.25 g / L) and stir for 10 min;
[0076] Step 2: Test and record the absorption peak of MO at this time;
[0077] Step 3: Quickly add PMS (0.5 g / L) into the round-bottom flask, take out 3 mL into the cuvette at 0 min, 1 min, 3 min, 5 min, 10 min, 15 min, and 20 min, and measure the peak shape of the UV-visible absorption spectrum of RR2 using a UV-visible photometer.
[0078] The mass of the catalyst in step 1 is 12.5 mg.
[0079] Example 7
[0080] The graphite carbon catalyst prepared by the present invention is used to generate singlet oxygen for the degradation of RB19.
[0081] The reaction mechanism of graphite carbon catalyst catalyzing PMS to produce active oxygen species to degrade RB19 is that in the presence of PMS, electrons are transferred through OO bond cleavage to activate PMS, thereby producing 1 O 2 Degrade RB19.
[0082] The steps of the graphite carbon catalyst catalyzing PMS to produce singlet oxygen to degrade RB19 are as follows:
[0083] Step 1: Add RB19 solution (50 mL, 50 mg / L) into a 100 mL round-bottom flask, add catalyst (0.25 g / L) and stir for 10 min;
[0084] Step 2: Test and record the absorption peak of RB19 at this time;
[0085] Step 3: Quickly add PMS (0.5 g / L) into the round-bottom flask, take out 3 mL at 0 min, 1 min, 3 min, 5 min, 10 min, and 15 min respectively, and add it into the cuvette. Use a UV-visible photometer to measure the peak shape of the UV-visible absorption spectrum of RB19.
[0086] The mass of the catalyst in step 1 is 12.5 mg.
[0087] Figure 6 It is a comparison diagram of the ultraviolet-visible light absorption spectra of AO7, RR2, MO and RB19 catalyzed by the graphite carbon catalyst prepared by the present invention to produce singlet oxygen from PMS.
[0088] Example 8
[0089] The steps of catalyzing PMS to produce singlet oxygen and degrading AO7 by the graphite carbon-carbon catalyst and repeating it 3 times are as follows:
[0090] Step 1: Add AO7 solution (50 mL, 50 mg / L) into a 100 mL round-bottom flask, add catalyst (0.25 g / L) and stir for 10 min;
[0091] Step 2: Test and record the absorption peak of AO7 at this time;
[0092] Step 3: Quickly add PMS (0.5 g / L) into the round-bottom flask, take out 3 mL into the cuvette at 0 min, 1 min, 3 min, 5 min, 7 min, 9 min, 11 min, 13 min, and 15 min, and measure the peak shape of the UV-visible absorption spectrum of AO7 with a UV-visible photometer.
[0093] Step 4: Centrifuge, wash, dry and place the graphite carbon catalyst in a muffle furnace for tempering at 600 °C for 2 h. Repeat steps 1-3 for 3 cycles.
[0094] The mass of the graphite carbon catalyst in step 4 is 12.5 mg.
[0095] Figure 7 This is a catalytic degradation rate diagram of the graphite carbon catalyst prepared by the present invention after repeated three cycles. The catalytic effect can be reflected by the degradation rate. It can be seen that the catalyst still maintains a good degradation effect after three cycles and can convert large molecular organic pollutants into green and pollution-free small molecular substances.
[0096] The above embodiments are only for illustrating the technical ideas and features of the present invention, and the contents are only preferred embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Within the technical scope disclosed by the present invention, equivalent changes or improvements made according to the technical solution and inventive concept of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a graphite carbon catalyst, characterized in that: The following steps are involved: Step 1, mixing p-nitrobenzaldehyde and pyrrole to prepare a mixed solution; Step 2, heating propionic acid to boiling, adding the mixed solution obtained in step 1 under reflux stirring, heating and boiling reaction for 1-2 hours, and cooling naturally after the reaction is completed; Step 3, adding methanol to the solution of step 2, mixing, letting stand and filtering, washing and collecting the filter cake, the filter cake is tetranitrophenylporphyrin; Step 4: The filter cake obtained in step 3 is vacuum dried and then graphitized at 600-900° C. The obtained material is washed with water and then dried to obtain the graphite carbon catalyst TNPP.
2. The method according to claim 1, characterized in that: The molar ratio of p-nitrobenzaldehyde to pyrrole in step 1 is 1:(1-2).
3. The method according to claim 1, characterized in that: In step 2, the volume ratio of propionic acid to the mixed solution is: (10-12.5):
1.
4. The method according to claim 1, characterized in that: The standing time in step 3 is 6-8 hours.
5. The method according to claim 1, characterized in that: In step 3, methanol and acetone solutions are used for repeated washing.
6. The method according to claim 1, characterized in that: In step 4, the vacuum drying temperature is 50-60° C. and the drying time is 6-8 h.
7. The method according to claim 1, characterized in that: During calcination in step 4, the material is first placed in a furnace, and then the temperature is raised at 2-5°C / min, and after reaching the target temperature, the temperature is kept constant for 2-4 hours.
8. The graphite carbon catalyst prepared according to the method according to any one of claims 1 to 7.
9. Use of the catalyst according to claim 8 in activating peroxymonosulfate to degrade organic pollutants.
10. The use according to claim 9, characterized in that: The organic pollutants include organic dyes AO7, Orange II, Reactive Blue 19, Methyl Orange, Reactive Red 2 and antibiotics.